Intermittent Fasting as A Method of Correcting Insulin Resistance in Type 2 Diabetes Mellitus - Angelina Gosudarskaia (Scientific Trends, 2025)
This article examines the mechanisms by which intermittent fasting influences tissue insulin sensitivity, pancreatic β- cell function, glucose levels, and glycated hemoglobin. Clinical trial data confirming the effectiveness of intermittent fasting in promoting weight loss and improving metabolic parameters in patients with type 2 diabetes are analyzed. Indications, contraindications, and the need for medical supervision when using intermittent fasting are discussed. The article highlights the potential of intermittent fasting as a complement to traditional therapy for type 2 diabetes.
Keywords: Type 2 diabetes mellitus, intermittent fasting, insulin resistance, glycemic control, β- cells, metabolic disorders, treatment, health.